1989
DOI: 10.1111/j.1365-2761.1989.tb00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of lake trout, Salvelinus namaycush (Walbaum), sac fry to dissolved gas supersaturation

Abstract: The tolerance of sac fry of lake trout, Salvelinus namaycush (Walbaum), to the acute effects of gas supersaturation, from hatching to swim-up, was tested using six gas levels, ranging from AP 8 to MS. Although many fish were moribund by the time the yolk was nearly absorbed, mortality during the 40-day study was negligible; survival to swim-up was 96-99%, including 99% survival at AP 148. Oi fish examined at AP 42, 40% showed bubble formation around the rim of the eye. Signs of trauma were greatest at AP 119 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Signs increased at AP 159; exoplhalmia was also 3%, but 20% of the fish had bubbles inside the mouth and another 20% had bubbles on the conjunctiva, or lower rim of the eye. A similar study with lake trout sac fry showed intracranial hemorrhages and histological formation of subcutaneous bubbles at gas levels as low as AP 8 (Krise and Herman 1989); visible signs of GBD included bubbles around the eye for fish held at AP 42. These bubbles indicated that subcutaneous damage to sac fry during a 15-d exposure can occur at low gas levels (AP 8), and visible signs of trauma in small lake trout can occur at AP 42 during a 40-d exposure.…”
Section: Resultsmentioning
confidence: 69%
“…Signs increased at AP 159; exoplhalmia was also 3%, but 20% of the fish had bubbles inside the mouth and another 20% had bubbles on the conjunctiva, or lower rim of the eye. A similar study with lake trout sac fry showed intracranial hemorrhages and histological formation of subcutaneous bubbles at gas levels as low as AP 8 (Krise and Herman 1989); visible signs of GBD included bubbles around the eye for fish held at AP 42. These bubbles indicated that subcutaneous damage to sac fry during a 15-d exposure can occur at low gas levels (AP 8), and visible signs of trauma in small lake trout can occur at AP 42 during a 40-d exposure.…”
Section: Resultsmentioning
confidence: 69%
“…Our test results describe the short-term mortality of and gas bubble formation in Atlantic salmon and lake trout exposed to high total gas pressure. Subcutaneous emphysema or hemorrhages in lake trout yolk-sac larvae exposed to AP = 8 mm Hg for 15 d (Krise and Herman 1989) indicated that internal damage may occur at low supersaturation levels without increasing fish mortality or resulting in visible signs of gas bubble disease. A comparison of tolerance of supersaturation under a standard set of conditions aids fish culturists by identifying the life stages most sensitive to gas supersaturation.…”
Section: Discussionmentioning
confidence: 99%
“…Exophthalmia results from gas pressure behind the eye (Dawley and Ebel 1975;Dawley et al 1976;Thorn et al 1978;Weitkamp and Katz 1980;Machado et al 1987;Krise andHerman 1989, 1991;Krise et al 1990). Supersaturation results in damage to the choroid of the eye, often resulting in hemorrhages (Stroud et al 1975;Thorn et al 1978;Machado et al 1987;Smith 1988;Krise and Herman 1989;Krise et al 1990). The progressive damage to the cornea resulting from long-term exposure to dissolved gas supersaturation greater than AP 4 probably increases the incidence of corneal rupture.…”
Section: Discussionmentioning
confidence: 99%
“…If gas supersaturation increases the percentage of lake trout with nuclear cataracts, the incidence of cataracts should increase as juveniles are exposed to progressively higher levels of gas supersaturation. Chronic exposure of juvenile salmonids to water supersaturated with nitrogen often results in gas bubble disease, which may include such eye damage as hemorrhaging, choroid and retinal damage, exophthalmia, and complete loss of the eyes (Poston et al 1973;Stroud et al 1975;Machado et al 1987;Smith 1988;Krise and Herman 1989;Krise et al 1990). Gas bubble disease may be followed by cataract development in the surviving fish.…”
mentioning
confidence: 99%